Inequalities in medicine use in Central Eastern Europe: an empirical investigation of socioeconomic determinants in eight countries - Vogler, Sabine (Int J Equity Health, 2015)
BACKGROUND: Equitable access to essential medicines is a major challenge for policy-makers world-wide, including Central and Eastern European countries. Member States of the European Union situated in Central and Eastern Europe have publicly funded pharmaceutical reimbursement systems that should promote accessibility and affordability of, at least essential medicines. However, there is no knowledge whether socioeconomic inequalities exist in these countries. Against this backdrop, this study analyses whether socioeconomic determinants influence the use of prescribed and non-prescribed medicines in eight Central and Eastern European countries (Bulgaria, Czech Republic, Hungary, Latvia, Poland, Romania, Slovenia, Slovakia). Further, the study discusses observed (in)equalities in medicine use in the context of the pharmaceutical policy framework and the implementation in these countries. METHODS: The study is based on cross-sectional data from the first wave of the European Health Interview Survey (2007–2009). Multivariate logistic regression analyses were carried out to determine the association between socioeconomic status (measured by employment status, education, income; controlled for age, gender, health status) and medicine use (prescribed and non-prescribed medicines). This was supplemented by a pharmaceutical policy analysis based on indicators in four policy dimensions (sustainable funding, affordability, availability and accessibility, and rational selection and use of medicines). RESULTS: Overall, the analysis showed a gradient favouring individuals from higher socioeconomic groups in the consumption of non-prescribed medicines in the eight surveyed countries, and for prescribed medicines in three countries (Latvia, Poland, Romania). The pharmaceutical systems in the eight countries were, to varying degrees, characterized by a lack of (public) funding, thus resulting in high and growing shares of private financing (including co-payments for prescribed medicines), inefficiencies in the selection of medicines into reimbursement and limitations in medicines availability. CONCLUSION: Pharmaceutical policies aiming at reducing inequalities in medicine use require not only a consideration of the role of co-payments and other private expenditure but also adequate investment in medicines and transparent and clear processes regarding the inclusion of medicines into reimbursement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12939-015-0261-0) contains supplementary material, which is available to authorized users.